Harvard Data Science Review 2022
DOI: 10.1162/99608f92.901255e7
|View full text |Cite
|
Sign up to set email alerts
|

Conduct and Implementation of Personalized Trials in Research and Practice

Abstract: The mainstay of evidence development in medicine is the parallel-group randomized controlled trial (RCT), which generates estimates of treatment efficacy or effectiveness for the average person in the trial. In contrast, personalized trials (sometimes referred to as 'single-person trials' or 'N-of-1 trials') assess the comparative effectiveness of two or more treatments in a single individual. These single-subject, randomized crossover trials have been used in a scattershot fashion in medicine for over 40 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The CENT guideline clearly describes a consensus on how to design, analyze, and report N-of-1 trials. 5 The increased availability over time of resources on the conductance of N-of-1 trials such as the CENT guideline and the user's guide on the design and implementation of N-of-1 trials by the Agency for Healthcare Research and Quality 47 is probably largely responsible for the positive correlation found between the quality of reporting scores and a more recent year of publication of the reviewed N-of-1 trials. The higher scores of quality of reporting and design and an N-of-1 trial design with multiple patients could be a consequence of the more systematic and thorough trial planning that is needed for these larger-scale clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The CENT guideline clearly describes a consensus on how to design, analyze, and report N-of-1 trials. 5 The increased availability over time of resources on the conductance of N-of-1 trials such as the CENT guideline and the user's guide on the design and implementation of N-of-1 trials by the Agency for Healthcare Research and Quality 47 is probably largely responsible for the positive correlation found between the quality of reporting scores and a more recent year of publication of the reviewed N-of-1 trials. The higher scores of quality of reporting and design and an N-of-1 trial design with multiple patients could be a consequence of the more systematic and thorough trial planning that is needed for these larger-scale clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…are made while the target individual is receiving, and not receiving, an intervention. This contrast between measures while on and off the intervention can then be exploited to quantify and characterize the individual’s response to the intervention but only if enough reliable measurements are made during each of the intervention periods and data analysis methods are used to control for confounding due to, for example, placebo or unmeasured covariate effects (Lillie et al, 2011 ; Kravitz et al, 2014 ; Wang and Schork, 2019 ; Kravitz and Duan, 2022 ). Note that many of the most widely used strategies for avoiding confounding in standard RCTs can be exploited in the design and execution of N-of-1 trials, such as randomizing the order in which the interventions are provided, blinding of the received interventions to the participants and/or researchers analyzing the data, washout periods to avoid carryover effects, etc.…”
Section: Basic N-of-1 Trial Designsmentioning
confidence: 99%
“…Note that many of the most widely used strategies for avoiding confounding in standard RCTs can be exploited in the design and execution of N-of-1 trials, such as randomizing the order in which the interventions are provided, blinding of the received interventions to the participants and/or researchers analyzing the data, washout periods to avoid carryover effects, etc. (Duan, Kravitz, and Schmid 2013;Duan et al 2022;Kravitz and Duan 2022;Kravitz, Duan, and Panel 2014;Lillie et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Further details about personalized trials are given in Cheung and Mitsumoto (2022), Davidson et al (2021), Duan et al (2013), Kravitz et al (2014), Kravitz and Duan (2022), Schmid and Yang (2021), and other articles in this special issue.…”
Section: Personalized Trials To Evaluate Treatment Effectivenessmentioning
confidence: 99%